DIKSI DAN GAYA BAHASA DALAM KHOTBAH PENDETA SEFNAT BABYS DI GPDI PERSAUDARAAN KECAMATAN LARIANG KABUPATEN MAMUJU UTARA - Tungga, Jefri; Syamsuddin, Syamsuddin; Ulinsa, Ulinsa (BAHASANTODEA, 2017)
The main problems of this research were (1) what is the form of diction in the sermon of Priest Sefnat Babys at GPDI Persaudaraan of Lariang District, North Mamuju Regency?. (2) How is the form of language style in Priest Sefnat Babys sermon at GPDI Persaudaraan in Lariang District, North Mamuju Regency?. This research also has two objectives, namely (1) describing the form of diction usage in Priest Sefnat Babys sermon at GPDI Persaudaraan in Lariang District, North Mamuju Regency. (2) Describing the form of language style in Priest Sefnat Babys sermon at GPDI Persaudaraan in Lariang District, North Mamuju Regency. This research was qualitative and used descriptive method. The source of the data in this research was Priest Sefnat Babys sermon at both Sunday and youth worship held on Saturday. The data were collected through recording, see and note technique. The instrument in this research was a cellphone to record Priest sermon and stationery to take notes. The data analysis technique in this research follows three stages, namely (1) data reduction, (2) data presentation, and (3) conclusion. In this research found the use of diction and forms of language in Priest Sefnat Babys sermon. The use of the diction form in Priest Sefnat Babys sermon is divided into two, namely based on the form of meaning and based on lexical. Dictation based on the form of meaning is divided into two namely denotative and connotative, while diction based on lexical forms are found in two forms, namely synonyms and antonyms. The use of the language style in Priest Sefnat Babys sermon is divided into three, namely the style of comparison, connection, and repetition. Comparative language styles are parables and metaphors, linking language styles namely antonomia, and repetition language styles namely epizeukis.